Soft computing architecture for speech enhancement in vehicular environment - Abdul Wahab Abdul Rahman (2008)
This thesis reviews various studies undertaken to examine the performance of the noise and other perturbations cancellers with respect to the speed of computation, effectiveness and residual errors produced.